2021
DOI: 10.3386/w28905
|View full text |Cite
|
Sign up to set email alerts
|

Funding Risky Research

Abstract: This paper was written for the NBER Entrepreneurship and Innovation Policy and the Economy (EIPE) meeting held April 27, 2021. The authors wish to thank the organizers, Josh Lerner and Scott Stern, for thoughtful comments on an earlier version. Comments from participants at the meeting are also highly appreciated. The authors also thank Katalin Karikó for helpful responses to our emails and her willingness to review our discussion of mRNA research. The views expressed herein are those of the authors and do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…In analyzing the case histories of the discovery of 21 important drugs, Cockburn and Henderson (1998) found that 14 of those drugs were discovered through 'fundamental scientific advances' or by 'mechanism-based screening'. A recent example of the importance of scientific research in drug discovery concerns the development of the messenger RNA (mRNA) COVID-19 vaccines by Pfizer-BioNTech and Moderna, which was the direct result of breakthrough scientific research by Katalin Karko and Drew Weissmann at the University of Pennsylvania on the functioning of mRNA-based vaccines (Franzoni et al, 2021).…”
Section: Science-based Drug Discoverymentioning
confidence: 99%
“…In analyzing the case histories of the discovery of 21 important drugs, Cockburn and Henderson (1998) found that 14 of those drugs were discovered through 'fundamental scientific advances' or by 'mechanism-based screening'. A recent example of the importance of scientific research in drug discovery concerns the development of the messenger RNA (mRNA) COVID-19 vaccines by Pfizer-BioNTech and Moderna, which was the direct result of breakthrough scientific research by Katalin Karko and Drew Weissmann at the University of Pennsylvania on the functioning of mRNA-based vaccines (Franzoni et al, 2021).…”
Section: Science-based Drug Discoverymentioning
confidence: 99%
“…In what follows, we present two real-world cases that illustrate how OIS approaches can tackle the disadvantages that exploration-oriented research faces in receiving external funding. Conventional funding schemes often fall short in distributing funding to projects characterised by higher levels of novelty, riskiness, and/or boundary crossing (Franzoni et al, 2021;Stephan et al, 2017). Even though OIS approaches are often analysed at the level of individual research projects and applied at one or more particular stages in the process of carrying them out (i.e., conceptualisation, exploration and/or testing, and documentation; Beck et al ( 2020)), we focus here on the system level, regarding funding distribution as a particularly strong lever for changing the research landscape due to the scale and power of its effects (i.e., affecting the early stages of numerous research projects with a single programme).…”
Section: Adapting Ambidexterity To Better Understand Developments In ...mentioning
confidence: 99%
“…Probably the most prominent class of phenomena in research on peer review are biases (for an overview, see Lee et al, 2013). While some of these phenomena are well-established, uncontested, and supported by robust evidence, such as the disagreement effect, 2 others are highly contested, such as gender bias (Sato et al, 2021), 3 or there is only preliminary and suggestive evidence −, for example, on conservatism (Franzoni et al, 2021;Guthrie et al, 2018b). In addition to biases, many other supposed, corroborated, or obvious phenomena can be found in the literature, such as overburdening (Kovanis et al, 2016) or lack of transparency (Horbach et al, 2020;Ross-Hellauer, 2017).…”
Section: Main Characteristics Of the Peer Review Literaturementioning
confidence: 99%
“…Evidence from grant peer review (e.g., Ayoubi et al, 2021;Boudreau et al, 2016) and journal peer review (Teplitskiy et al, 2021) seem to support the theory. Franzoni et al (2021) devised a framework to analyze why funding agencies may eschew risky research. The framework includes factors within the research system that might contribute to risk aversion (accountability, short-term thinking, no tolerance for failure, bibliometric indicators, soft-money positions) and nine hypotheses on the behavior of principial -11 -investigators (refraining from submitting risky proposals, loss aversion), panelists (insurance agent view, bibliometric screening, risk-biased panelists), and funding agencies (no portfolio approach, interdisciplinary bias, review protocols concealing uncertainty, stress on agreement).…”
Section: Some Theoretical Efforts On Peer Reviewmentioning
confidence: 99%